Interakcja w klasie językowej - metodologia badawcza - Targońska, Joanna (Neofilolog, 2019)
The present article is devoted to the discussion of the methodology of research into interaction in the foreign language classroom. It discusses selected methods which can be employed to allow a complete and reliable monitoring of the varied interactions which can occur during foreign language lessons. The paper concludes with an attempt at formulating some general principles relating to researching classroom interaction.